1978
DOI: 10.2105/ajph.68.2.169
|View full text |Cite
|
Sign up to set email alerts
|

The medical impact of an antepartum program for pregnant adolescents: a statistical analysis.

Abstract: Rates went up with age and were higher for males than females, for blacks than whites, and for Philadelphia as compared with non-Philadelphia residents. As of December 31, 1974, 62 per cent of the patients were on center maintenance, 28 per cent were on home dialysis, and 10 per cent had received a transplant. It was concluded that there is a great need for further research to delineate the role of the various factors which lead to end-stage renal disease with the goal of preventing the development of this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…As a result, the rate of complications dropped markedly. 8,9 Thus the complications were mainly attributed to absence of prenatal care in this population.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, the rate of complications dropped markedly. 8,9 Thus the complications were mainly attributed to absence of prenatal care in this population.…”
Section: Discussionmentioning
confidence: 88%
“…Also, many studies have investigated methods to improve the poor outcomes. These methods included the use of nurse‐midwives, nurse practitioners, multi‐disciplinary teams, and special educational programs 1–13 …”
mentioning
confidence: 99%
“…The potential for specialized prenatal intervention to reduce rates of maternal and infant problems has been evaluated by programs such as the Young Women's Clinic at the University of California, 2 Booth Maternity Center in Philadelphia, 6 Adolescent Obstetric Clinic at the Medical University of South Carolina, 7 Young Mothers Clinic at the University of Colorado, 10 and the Goldfarb Adult Development Clinic, Houston, Texas 11 . The program evaluations revealed decreased rate of prenatal urinary tract infection 8 and increased rate of prenatal and postpartum visits 6,11 . The adolescents experienced less medication while in labor 10 and a decreased incidence of labor and delivery complications 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy outcomes among adolescent women have been shown to be improved by providing prenatal care. Some studies have suggested that offering specialized comprehensive care can improve outcomes even further 1,2 . Because care of this type usually is labor intensive, comprehensive programs for pregnant teenagers are more expensive, in both their inception and maintenance, than are standard prenatal care programs.…”
mentioning
confidence: 99%